Steel A-braced frame upgrade performance under various load characteristics. (December 2020) - Halim, H.; Hsu, H.-L.
Abstract: This study evaluated innovated A-braced frame design performance under cyclic load and twelve far-field and near-field earthquake ground motions. The proposed A-brace design combined pre-deformed brace segments, steel curved damper and lever mechanism to amplify steel curved damper deformation for effective energy dissipation. A series of cyclic loading tests on steel moment resisting frames with the proposed A-braces were conducted first. The cyclic load test results showed that A-braced frames exhibited higher stiffness than the moment resisting frame in both elastic and inelastic stages to effectively reduce the structural deformation. Significant strength and energy dissipation enhancements were achieved in A-braced frames, with maximum gains reaching 2.31 and 1.94 times, respectively, above those of the moment resisting frame. Seismic performance evaluation on multi-story framed structures revealed that lower structural base shear, reduction in story drift, approximately 30.86%, 27.61% and 27.51% for the 10, 6 and 3-story frames, respectively, and plastic hinge development elimination to prevent structural failure were achieved simultaneously when the A-brace was adopted. The A-braced frame performance enhancements under cyclic load and various earthquake ground motions effectively justified proposed method applicability to seismic structural design. Graphical abstract: Unlabelled Image Highlights: Innovated braced frame design with amplified deformation mechanism in damper was proposed and validated. Important experimental information on cyclic performance of A-braced frames was presented. Effective viscous damping and energy dissipation were achieved in the proposed A-braced frames. Effective seismic performance evaluation on A-braced frames was conducted. Applicability of A-brace to seismic structural design was validated.